Comment on "Extent of conjugation in diazonium-derived layers in molecular junction devices determined by experiment and modelling" by C. Van Dyck, A. J. Bergren, V. Mukundan, J. A. Fereiro and G. A. DiLabio, Phys. Chem. Chem. Phys., 2019, 21, 16762. Issue 37 (14th September 2020) - McCreery, Richard L.; Saxena, Shailendra K.; Supur, Mustafa; M. Tefashe, Ushula
Abstract : Misinterpretation of scanning tunnelling microscopy results and sampling error yielded incorrect conclusions about the flatness of a carbon electrode substrate used for molecular electronic devices. Abstract : Misinterpretation of scanning tunnelling microscopy results yielded incorrect conclusions about the flatness of a carbon electrode substrate used for molecular electronic devices. Furthermore, the results are not supported statistically and likely not representative of materials used in numerous publications.